Social Media Instagram as a News Reference for Journalism Students - Aulia Maharani, Nisa; Wahyunengsih, Wahyunengsih (LPPM Universitas Jambi, 2024)
This study investigates the use of Instagram as a reference source by journalism students in the digital era. As technological advancements continue to transform communication landscapes, social media has emerged as a critical medium for information dissemination. Using a qualitative research design, data were gathered through questionnaires and interviews with journalism students. The findings indicate that Instagram significantly supports students’ news production processes, primarily due to its accessibility, immediacy, and diverse content. Students are not merely passive recipients of information; they actively engage with and disseminate news obtained from the platform. Furthermore, the study finds that information sourced from Instagram is increasingly perceived as credible and is integrated into journalistic writing practices. These results underscore the platform’s expanding role in shaping contemporary news-gathering behaviors among aspiring journalists, reflecting broader shifts in media consumption patterns in the digital age.